Development of Science Process Skills and Learning Achievement Using Flipped Classroom Learning Management through Inquiry-Based Learning for Grade 8 Students - Yolradee Supornpanitkul; Apantee Poonputta; Orrasa Prasitnok (Journal of Education in Science, Environment and Health)
The objectives of this research are: (1) to develop a flipped classroom learning plan using inquiry-based learning on the topic of substance separation for Grade 8 students, to achieve effectiveness according to the 75/75 criteria; (2) to compare science process skills and learning achievement before and after implementing the developed learning plan. The study included 45 Grade 8 students from a high school in Khon Kaen Province, Thailand, during the second semester of the 2022 academic year. The students were chosen using cluster random sampling. The research tools included: (1) six flipped classroom learning management through inquiry-based learning on the topic of mixture separation, totaling 11 hours; (2) a multiple-choice test with 30 questions on the topic of mixture separation to measure learning achievement; and (3) a multiple-choice test with 30 questions to assess science process skills. The statistical analysis includes mean, percentage, standard deviation, and hypothesis testing with Hotelling’s T-Square. The research findings were: (1) the flipped classroom learning plan using inquiry-based learning had an effectiveness of 89.2/77.5; (2) the learning achievement and science process skills of students after implementing the developed learning plans were significantly higher than before, with statistical significance at the .05 level.